Confined granular flow in silos : experimental and numerical investigations - Tejchman, Jacek (Springer Series in Geomechanics and Geoengineering, 2013)
During confined flow of bulk solids in silos some characteristic phenomena can be created, such as: -         sudden and significant increase of wall stresses, -         different flow patterns, -         formation and propagation of wall and interior shear zones, -         fluctuation of pressures and, -         strong autogenous dynamic effects. These phenomena have not been described or explained in detail yet. The main intention of the experimental and theoretical research presented in this book is to explain the above mentioned phenomena in granular bulk solids and to describe them with numerical FE models verified by experimental results.